Diagnostic accuracy of foot length measurement for identification of preterm newborn in rural Sindh, Pakistan - Nick Brown; Andreas Mårtensson; Sarah Saleem; Shiyam Sundar Tikmani; Alijaan Inayat; Thomas Mårtensson (BMJ Publishing Group, 2024)
Introduction Assessing gestational age accurately is crucial for saving preterm newborns. In low and middle-income countries, such as Pakistan, where access to antenatal ultrasonography (A-USG) is limited, alternative methods are needed. This study evaluated the diagnostic accuracy of foot length (FL) measurement for identifying preterm newborns in rural Pakistan using A-USG as the reference standard.Methods A test validation study was conducted between January and June 2023 in rural Sindh, Pakistan, within the catchment area of the Global Network for Maternal Newborn Health Registry, Thatta. Singleton newborns whose mothers had an A-USG before 20 weeks of gestation were enrolled. A research assistant measured FL three times using a rigid transparent plastic ruler within 48 hours of birth and the average FL was reported. Sensitivity, specificity, positive and negative predictive values (PPV, NPV) and likelihood ratios were calculated. The optimal FL cut-off for the identification of preterm newborns was determined using the Youden Index.Results A total of 336 newborns were included in the final analysis, of whom 75 (22.3%) were born before 37 weeks of gestation. The median gestational age of the newborns was 38.2 weeks, and the median FL was 7.9 cm. The area under the curve was 97.6%. The optimal FL cut-off for identifying preterm newborns was considered as ≤7.6 cm with a sensitivity of 90.8%, specificity of 96.0%, PPV of 86.7% and NPV of 97.3%. A lower cut-off of ≤7.5 cm had a sensitivity of 95.4%, specificity of 84.0%, PPV of 63.1% and NPV of 98.5%.Conclusion In conclusion, this study highlights the utility of FL measurement for identifying preterm newborns in rural settings where A-USG is unavailable before 20 weeks of gestation. Optimal cut-offs of ≤7.6 and ≤7.5 cm provide a simple, cost-effective and reliable tool for clinicians and frontline healthcare providers in rural areas, respectively.Trial registration number NCT05515211.